Assessing the reliability of abdominal adiposity measurements by transabdominal ultrasound in first trimester pregnancies with sonographers of varying experience levels - Noppasin Khwankaew; Nattraporn Srisovanna; Ninlapa Pruksanusak (PLoS ONE, 2025)
Objective Given the growing evidence linking increased abdominal adiposity in early pregnancy to a higher risk of developing gestational diabetes mellitus (GDM), this study aims to evaluate the reliability of the sonographic measurements of abdominal adiposity during the first trimester of pregnancy, comparing the performance of sonographers with varying levels of experience. Methods A cross-sectional study was conducted on singleton Asian pregnant women with gestational ages between 11 and 14 weeks. Transabdominal ultrasound measurements of abdominal adiposity were performed by three sonographers with different experience levels, including measurements of subcutaneous fat thickness (SFT), visceral fat thickness (VFT), and preperitoneal fat thickness (PFT) using three techniques. Intra- and interobserver reliability were assessed using intraclass correlation coefficient (ICC) with a 95% confidence interval. Spearman pairwise correlation coefficients were used to analyze the correlation between maternal body composition and the sonographic measurements of abdominal adiposity. Result Ninety pregnant women participated. The overall ICCs indicated excellent intraobserver reliability for all parameters, with VFT measurement showing slightly lower reliability for less experienced operators. Interobserver reliability was excellent for all measurements except VFT, which showed good reliability between the most and least experienced operators. VFT correlated significantly with maternal waist-to-hip ratio (WHR). Conclusion Sonographic measurements of abdominal adiposity during the first trimester show high reliability, particularly when performed by experienced sonographers. Notably, VFT measurement displayed a significant positive correlation with maternal WHR, highlighting its potential as an indicator of central adiposity.